Shrouded History: The Canadian Film and Photo Unit, Records Creation, Reuse, and the Recontextualizing of "Lost" Audiovisual Heritage - Cook, Sarah (Archivaria, 2017)
This article provides a history of the record created by the film unit of the Canadian Army during the Second World War. Through a reading of the records (photos, textual records, etc.), the author rebuilds the context of creation of the audiovisual records, their custodial history after the war, and their postcustodial experience. The contextualizing postcustodial history is relevant to understanding not only the Canadian Film and Photo Unit heritage, but also other aspects of Canada’s audiovisual history. Canada’s early audiovisual historical record is very much affected by its later custodians and archives. As such, this article is a history of the making of a historical record during the Second World War as well as a history of recordkeeping after the war. RÉSUMÉ Cet article présente un historique des documents d’archives créés par l’unité de film et de photographie de l’Armée canadienne pendant la Seconde Guerre mondiale. En examinant les documents d’archives (photos, documents textuels, etc.), l’auteure rétablit le contexte de création des documents audio-visuels, l’historique de leur conservation après la guerre et celle de leur « post-conservation » (« postcustodial experience »). L’historique du contexte de « post-conservation » (« contextualizing postcustodial history ») est pertinent afin de comprendre non seulement le patrimoine de l’Unité de film et de photographie de l’Armée canadienne, mais aussi d’autres aspects de l’histoire audio-visuelle canadienne. Les archives des premiers documents audio-visuels du Canada ont été très affectées par leurs conservateurs et leurs centres d’archives. Ainsi, cet article se veut l’histoire de la création d’archives historiques pendant la Seconde Guerre mondiale, aussi bien que l’histoire de la tenue de documents dans l’après-guerre.